A snapshot of online wildlife trade: Australian e-commerce trade of native and non-native pets. (June 2023) - Toomes, Adam; Moncayo, Stephanie; Stringham, Oliver C.; Lassaline, Charlotte; Wood, Lisa; Millington, Mariah; Drake, Charlotte; Jense, Charlotte; Allen, Ashley; Hill, Katherine G.W.; García-Díaz, Pablo; Mitchell, Lewis; et al.
Abstract: The international trade of non-domesticated pets impacts both conservation and biosecurity via the harvest and release of live animals beyond their native distributions. The extent to which individual countries mitigate these impacts via regulation of trade is inconsistent, as is their capacity to monitor internet facilitated trade. We investigated the online trade of vertebrate pets within Australia, a country with a reputation for relatively stringent pet-importation regulations and world-class border biosecurity. Using semi-automated data mining (i.e., webscraping) techniques, we collected online pet trade data over the course of 14 weeks from 12 Australian e-commerce platforms selected using an a priori set of search terms. We analysed spatial, temporal and taxonomic biases in trade and identified instances of high rates of trade in: (i) threatened species, (ii) non-native species, (iii) and species not permissible for live import. We identified over 100, 000 individual live animals across 1192 species, including: 667 non-native species for sale within Australia from 03/12/2019 to 20/03/2020 (mammals were excluded from our analysis). Our findings constitute a much greater scale (in terms of abundance and richness) of non-native species trade than previously recorded in Australia. Substantial changes to legislative control of domestically traded pets are needed at the national level to reduce the volume of non-native pets that may contribute to the establishment of invasive species in Australia. We suggest that contemporary examples of permit systems applied to native taxa may provide a valuable template for the implementation of such changes. Highlights: The vertebrate pet trade in Australia is subject to strict import laws, but inconsistent domestic trade regulations. We use webscrapers to collect online pet trade data from 12 Australian websites over 14 weeks prior to COVID disruptions. We found 1192 species being within Australia, including 667 non-native species and 81 threatened species. The trade in non-native pets is highly unregulated, including 279 species that are illegal to commercially import. Trade of taxonomically undescribed taxa was widespread, with 'pseudo-taxonomic' names used by hobbyists instead.